2018
DOI: 10.1016/j.hemonc.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Kidney dysfunction after hematopoietic cell transplantation-Etiology, management, and perspectives

Abstract: Kidney dysfunction is a common complication of hematopoietic cell transplantation (HCT) with proven negative impact on early and long-term mortality. Causes of this complication are diverse, usually overlapping, and poorly understood. Therefore, management implicates multidirectional investigations and simultaneous treatment of suspected causes. The etiology is frequently unconfirmed due to a lack of specific markers and prevalence of contraindications to renal biopsy among HCT recipients. Herein, we provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 80 publications
0
11
0
1
Order By: Relevance
“…In observational studies, CKD has shown a variable incidence in HSCT patients, varying between 18-66%, due to the different parameters used for CKD definition and the differences in the duration of follow-ups ( 69 71 ). In general, renal dysfunctions are multifactorial complications that can be caused by pre-transplant underlying diseases and comorbidities, conditioning regimens, transplant complications and prophylaxis treatments ( 72 ).…”
Section: Hsct-derived Endocrine Sequelae Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…In observational studies, CKD has shown a variable incidence in HSCT patients, varying between 18-66%, due to the different parameters used for CKD definition and the differences in the duration of follow-ups ( 69 71 ). In general, renal dysfunctions are multifactorial complications that can be caused by pre-transplant underlying diseases and comorbidities, conditioning regimens, transplant complications and prophylaxis treatments ( 72 ).…”
Section: Hsct-derived Endocrine Sequelae Pathophysiologymentioning
confidence: 99%
“…Pre-existing renal pathologies, such as glomerulonephritis, develop from hematological malignancies for which HSCT intervention is planned, therefore, the underlying hematological diseases already provoke renal lesions before HSCT, increasing in this way the risk of severe renal failure in the long term HSCT survival ( 78 ). Moreover, comorbidities such as diabetes, hypertension, and arteriosclerosis have been shown to further contribute to renal failure after transplant ( 72 ).…”
Section: Hsct-derived Endocrine Sequelae Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…51 Chronic kidney disease (CKD) is an important late morbidity among survivors of allogeneic HCT and occurs at a higher incidence (14%) in this population as compared with autologous HCT recipients (4%). 52 In addition, although reduced intensity conditioning (RIC) regimens have a lower treatment-related mortality compared with myeloablative conditioning (MAC) regimens, the incidence of CKD is similar in allogeneic recipients receiving either RIC or MAC regimens. 53 CKD increases the risk of developing cardiovascular disease, infections, and other cancers; long-term outcomes also include the development of end-stage renal disease (ESRD).…”
Section: Renal Complicationsmentioning
confidence: 99%
“…A DRC é uma possível complicação do TCTH e a consequência mais grave é uma doença renal em estágio terminal (DRET) 3 . A identificação dos fatores de risco, o diagnóstico precoce e o tratamento da DRC antes ou após o TCTH-alo são importantes para um transplante seguro 4 .…”
Section: Introductionunclassified